(3fRgI GdCHUGQ aj CYeGd Gddjd hGdfgGQs - (3eMeO GdhaGFjs
(3ChdgG (B:s
(3ai GdJYGOjd GdCUdjg GdJi gi bHd JbQjHgG GdTeS hSW jfbUGf OQLJGf s
(3BNQgG (B:s
(3hBNPfG eG HERGA GdHGbi Hf GdGNJdGa s
(3eMeO GdhaGFi JdejP GdTjN eMeO Hf GdaJM GdUhais
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B150 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B102 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs